The emerging role of Slit-Robo pathway in gastric and other gastro intestinal cancers. Issue 1 (December 2015) - Huang, Tingting; Kang, Wei; Cheng, Alfred; Yu, Jun; To, Ka
Abstract Gastric cancer remains one of the most common cancers worldwide and one of the leading cause for cancer-related deaths. Due to the high frequency of metastasis, it is still one of the most lethal malignancies in which kinds of signaling pathways are involved in. The Roundabout (ROBO) receptors and their secreted SLIT glycoprotein ligands, which were originally identified as important axon guidance molecules, have implication in the regulation of neurons and glia, leukocytes, and endothelial cells migration. Recent researches also put high emphasis on the important roles of the Slit-Robo pathway in tumorigenesis, cancer progression and metastasis. Herein we provide a comprehensive review on the role of these molecules and their associated signaling pathway in gastric and other gastrointestinal cancers. Improved knowledge of the Slit-Robo signaling pathway in gastric carcinoma will be useful for deep understanding the mechanisms of tumor development and identifying ideal targets of anticancer therapy in gastric carcinoma.